Associations of school tobacco policies and legislation with youth smoking: a cross-sectional study of Danish vocational high schools - Janne Tolstrup; Morten Hulvej Rod; Susan Andersen; Veronica Pisinger (BMJ Open)
Background In vocational high schools, the prevalence of smoking is high (nearly 40% daily smoking in Danish vocational high schools). Schools are increasingly adopting school tobacco policies (STPs) and a national law on smoke-free school grounds has been implemented. Our objective was to explore the extent of STPs in vocational schools and examine the association of STPs and smoke-free school grounds legislation with student smoking.Methods We used data from the cross-sectional Danish National Youth Study 2014, including 5013 vocational high school students (76% male) at 40 campuses. Implementation of STPs was measured by questionnaires to principals and field observations of smoking practices were conducted. Logistic regression models assessed whether STP characteristics were associated with students’ current smoking (ie, daily and occasional) compared with non-current smoking. Negative binominal regression models assessed cigarettes per day among daily smokers.Results Schools covered by the national law on smoke-free school ground had more comprehensive STPs than schools not covered by the law. Student smoking was observed on 78% of campuses, with less visibility of smoking in schools covered by the national law (69% vs 83%). Current smoking was lower for students attending a school covered by the national law (OR=0.86, 95% CI 0.75 to 0.97). Students who attended schools that allowed teacher–student smoking were more likely to smoke (OR=1.13, 95% CI 1.01 to 1.27).Conclusions A law on smoke-free school grounds was associated with less current smoking in vocational high schools, while school norms that are supportive of teacher-student smoking were associated with greater odds of current smoking. Visibility of student smoking was less prevalent at schools covered by the law on smoke-free school grounds; nevertheless, the visibility of smoking was high. Better enforcement or an extension of the current law on smoke-free school grounds is recommended.